2000
DOI: 10.1002/jlb.67.6.808
|View full text |Cite
|
Sign up to set email alerts
|

Exoenzyme S from Pseudomonas aeruginosa induces apoptosis in T lymphocytes

Abstract: Exoenzyme S from Pseudomonas aeruginosa is a unique T cell mitogen; it is a powerful immunostimulus that activates a large proportion of T cells, but results in delayed and reduced lymphocyte proliferation. This study was performed to explain the discrepancy between early T cell activation and subsequent proliferation. Studies revealed that exoenzyme S induced rapid and unsustained surface expression of CD69, but could not induce interleukin-2 receptor ␣ (IL-2R␣) upregulation on T cells. IL-2 was undetectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 70 publications
0
23
0
1
Order By: Relevance
“…Nonetheless, it remains a partially elucidated picture how the "on and off" switch of ExoS secretion in susceptible human host correlates with the progression of the P. aeruginosa infection. In recent years, increasing numbers of studies, both in vitro or in vivo, describe apoptosis induction by P. aeruginosa (17,23,36,38,46,77,89); some of the studies identified a variety of apoptosis-inducing factors from the bacterium (2,7,8,34,47,50,88). Bruno et al (7) and we (50) first reported ExoS as one of these factors.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, it remains a partially elucidated picture how the "on and off" switch of ExoS secretion in susceptible human host correlates with the progression of the P. aeruginosa infection. In recent years, increasing numbers of studies, both in vitro or in vivo, describe apoptosis induction by P. aeruginosa (17,23,36,38,46,77,89); some of the studies identified a variety of apoptosis-inducing factors from the bacterium (2,7,8,34,47,50,88). Bruno et al (7) and we (50) first reported ExoS as one of these factors.…”
Section: Discussionmentioning
confidence: 90%
“…We intended to further dissect signaling pathways involving ExoSmediated apoptosis. P. aeruginosa possesses a large array of virulence factors that can cause host cell toxicity to certain extend (2,7,8,34,47,50,60,67,75,88,93,95); at the same time, it has not been demonstrated conclusively whether ExoSdependent apoptosis induction coincides with necrosis-like cell death resulting from the diverse effects on cellular components by ExoS or whether apoptosis is secondary to that event. It is therefore important to determine whether the ExoS protein alone is sufficient to induce apoptosis in host cells independent of other bacterial virulence components.…”
Section: Transiently Expressed Exos Induces Apoptosis In Hela Cellsmentioning
confidence: 99%
“…Recently, Usher and colleagues have reported induction of neutrophil apoptosis by Pseudomonas pyocyanin and suggested it as a potential mechanism of persistent infection (41). In addition, a variety of cells, including macrophages, epithelial cells, fibroblasts, and T cells, have been shown to be targets of P. aeruginosa-induced apoptosis (2,12,18). The present study showed that macrophages and neutrophils are susceptible, while epithelial cells are resistant, to 3-oxo-C 12 -HSL-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Exoenzyme-S-induced activation of T cells is neither dependent upon nor inhibited by ADP-ribosyltransferase activity, and this activity is present in exoenzyme S from both purified and recombinant sources (7). Further, we have found that activation by exoenzyme S induces T-cell apoptosis (6). The current studies were performed to determine whether this T-cell activation culminates in the induction of cytokines that have the potential of influencing immunoinflammatory responses or whether apoptosis precludes cytokine transcription.…”
mentioning
confidence: 93%